2013
DOI: 10.1209/0295-5075/103/47011
|View full text |Cite
|
Sign up to set email alerts
|

An electrocaloric device demonstrator for solid-state cooling

Abstract: A prototype device was designed to demonstrate electrocaloric cooling of Pb(Mg 1/3 Nb 2/3 )O3-PbTiO3 70/30 single crystals as active cooling elements. The test section was devised to investigate potential bulk cooling effects of the single-crystal materials under repeated electric-field cycles. Despite the low electrocaloric temperature changes measured by indirect method (ΔTmax = 2.7 K in 240 V), the test materials showed significant cooling rates under optimized device parameters compared to those of natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Kleemann et al [26] reported a spontaneous polarization of 37 C cm −2 . The variation in these values is due to difference in the samples, 1 The feram software is distributed freely under the GNU general public license at http://loto.sourceforge.net/feram/. 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kleemann et al [26] reported a spontaneous polarization of 37 C cm −2 . The variation in these values is due to difference in the samples, 1 The feram software is distributed freely under the GNU general public license at http://loto.sourceforge.net/feram/. 1.…”
Section: Resultsmentioning
confidence: 99%
“…The framework for the molecular dynamics (MD) simulation and effective Hamiltonian is encoded in the software package feram [18,19]. 1 Methods for predicting the ECE are described in detail in Ref. [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing interest for the use of electrocaloric materials for cooling devices could be observed after an adiabatic temperature change of 12 C was obtained in PbZrTiO thin films (Mischenko et al, 2006). The investigations of Lu et al (2010) show a significant electrocaloric effect in relaxor ferroelectrics, furthermore Jia and Sungtaek Ju (2012) and Chukka et al (2013) developed solid-state cooling devices to study the electrocaloric cooling process. The elastocaloric effect of CuZnAl shape memory alloys (SMA's) has been investigated by Bonnot et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the adaptation of the material properties to the specific requirements in terms of elastocaloric refrigeration (Bechtold et al, 2012) a comprehensive scientific test setup is needed to investigate the cooling process and optimize the process cycle. In the field of magnetic refrigeration, experimental devices have been developed to investigate the influence of the operating conditions on the process functions (work and heat) (Tu sek et al, 2013), (Chukka et al, 2013). Similar setups have been designed for electrocaloric refrigeration (M. O zbolt et al, 2014a), (O zbolt et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%